A Secure Technique for Microvascular Anastomosis in Arteries with Intimal Dissection: Intimal Sleeve Fold-Over Technique. Issue 4 (April 2016) - Hsieh, Tung-Ying; Huang, Yu-Hao; Chang, Feng-Shu; Chang, Chih-Hau; Chen, Ko-Kang; Huang, Shu-Hung; Lai, Chung-Sheng; Lin, Sin-Daw; Chang, Kao-Ping
Abstract : Background: Intimal dissection can cause an irregular internal surface with intimal flaps and subendothelial collagen exposure. This has been associated with a high risk of thrombosis. Trimming the artery to a healthy level is routinely recommended to avoid intimal dissection. However, this method is limited when there is inadequate vascular length to work with. Methods: We dealt with an artery exhibiting severe intimal dissection by using a new suture technique: the intimal sleeve fold-over technique. Severe arterial intimal dissections were observed in 9 (6.9%) of 130 arterial microvascular anastomoses in free flap reconstruction for oral cancer patients from January 2013 to December 2013. We used this technique in 6 of the 9 patients. Results: All 6 patients were discharged as scheduled without perioperative problems and complications during follow-ups. The mean diameters of the recipient and pedicle arteries with intimal dissection were 2.13 and 2.20 mm. The mean time for performing sleeve fold-over procedure of on each artery was 5.1 minutes. Conclusions: A secure intima-to-intima contact can be achieved using this technique. This technique can provide an alternative method to intimal dissection when the length of the artery is limited. Abstract : Supplemental Digital Content is available in the text.